2007
DOI: 10.1097/01.ccm.0000253397.42079.d5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of statin therapy on infection-related mortality in patients with atherosclerotic diseases*

Abstract: Therapy with statins may be associated with a reduced risk of infection-related mortality. This protective effect is independent of all known comorbidities and dissipates when the medication is discontinued. If this finding is supported by prospective controlled trials, statins may play an important role in the primary prevention of infection-related mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
2
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 34 publications
4
81
2
3
Order By: Relevance
“…Guidelines suggest that diabetics routinely be provided medications that impact on survival (HMG CoA reductase inhibitors, ACE, AR�, asprin and calcium channel blockers). For example, mortality is significantly reduced in bacteremic patients who had previously been treated with HMG CoA reductase inhibitor therapy [19][20][21][22] . The attributable mortality was reduced from 20% to 3% in one study [19] and hospital mortality was reduced from 23.1% to 10.�% in a second study (OR 0.39, 95% CI: CI: 0.17-0.91, , P �� 0.05) �� 0.05) 0.05) 0.05) [20] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guidelines suggest that diabetics routinely be provided medications that impact on survival (HMG CoA reductase inhibitors, ACE, AR�, asprin and calcium channel blockers). For example, mortality is significantly reduced in bacteremic patients who had previously been treated with HMG CoA reductase inhibitor therapy [19][20][21][22] . The attributable mortality was reduced from 20% to 3% in one study [19] and hospital mortality was reduced from 23.1% to 10.�% in a second study (OR 0.39, 95% CI: CI: 0.17-0.91, , P �� 0.05) �� 0.05) 0.05) 0.05) [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, if HMG CoA reductase inhibitor therapy was continued during the hospital stay, the OR for mortality was greatly reduced (0.0��� 95% CI: 0.01-0.44, CI: 0.01-0.44, 0.01-0.44, P �� 0.01) �� 0.01) 0.01) 0.01) [20] . Even if prior HMG CoA reductase inhibitor therapy was stopped upon admission to the hospital, a mortality benefit persisted (�.37 risk adjusted OR, P �� 0.05) 0.05) 0.05) [21] . Prior ACE therapy [19] or AR� therapy [22] appear to have similar mortality benefits in users as compared to non-users.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies have shown that patients taking statin therapy for hypercholesterolemia or ischemic heart disease have reduced incidence and mortality from sepsis compared with those who were not treated with statins (Almog et al, 2004(Almog et al, , 2007. Likewise, previous studies in mice have shown that statin treatment extends survival after the induction of sepsis, infection, and endotoxin challenge (Merx et al, 2004(Merx et al, , 2005Yasuda et al, 2006;Ayyadurai et al, 2010;Rosch et al, 2010;Shinozaki et al, 2010;Takano et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…They also reduce mortality 4.5 times in septic patients with atherosclerosis [74], 2 times in patients with pneumonia [75], 2.3 times suspected infection releated mortality in the emergency department [76]. In contrast, some other studies reported no improve on clinical outcomes with statins, and are not associated with reduced mortality or need for admission to an ICU in patients with pneumonia; and reports of benefit in sepsis attributed to confounding variables [77;78].…”
Section: Reducing Mortality and Improving Outcomesmentioning
confidence: 99%